Functional Characteristics of the Assessment Tool System in the Context of Modular Educational Programs Implementation - E. I. Sakharchuk; E. A. Baykina (Высшее образование в России, 2020)
The modular organization of the educational process assumes the existence of a system of assessment tools that provides multidimensional assessment of the process of competencies development among students at different stages of training. However, at present, the design of assessment tools represents the most problematic area for the academic community, since the scientific foundations of this process remain insufficiently explored. The purpose of our research is to study the functional characteristics of the assessment tools system in the structure of a competency-based educational program of modular architecture. To achieve this goal, the following methods were used: a) a theoretical analysis of the pedagogical literature and normative documents on the topic, b) an analysis of existing practices in the development of a system of assessment tools, c) a generalization of the progressive practice of using pedagogical design, assessment and diagnostic procedures of modular architecture by teams of reputable universities. A change in the approach to designing the university’s control and evaluation activities entails changes in the functional characteristics of its elements. The content of the functions of the assessment tools system is predetermined by the purpose, goals and objectives assigned to the system. Changing the goals and objectives of the assessment procedures entails a qualitative change in functions, which demonstrates the presence of a systemic relationship between these elements and determines the significance of the functions. The results obtained during the study can be used by university teachers as a guide when designing their own model of the assessment tools system in the context of the transition to the modular construction of educational programs, which, in general, initiates changes in the field of control and assessment.